Constructing a three-dimensionally ordered macroporous LaCrOδ composite oxide via cerium substitution for enhanced soot abatement. Issue 11 (2nd May 2017) - Feng, Nengjie; Chen, Chong; Meng, Jie; Liu, Geng; Fang, Fan; Ding, Jing; Wang, Lei; Wan, Hui; Guan, Guofeng
Abstract : The addition of Ce into Cr-based perovskite restrained the growth of the crystal size and delayed the transformation from LaCrO4 to LaCrO3, and thus, the 3DOM structure was maintained even after calcination at 800 °C. Abstract : La1− x Ce x CrO δ (0 ≤ x ≤ 0.3) composite oxides with three-dimensionally ordered macroporous (3DOM) structures were constructed by a colloidal crystal template method and characterized via XRD, FT-IR, FESEM, N2 adsorption–desorption, XPS, H2 -TPR, and O2 -TPD techniques. The catalytic performances of the as-prepared samples for soot oxidation were further evaluated. In the case of unsubstituted species, the crystal size of LaCrO3 increased with the increasing calcination temperature, which resulted in the destruction of the 3DOM structure. The introduction of Ce delayed the crystal phase transition from LaCrO4 monazite to LaCrO3 perovskite and inhibited the growth of the crystal size; thus, the collapse of the 3DOM structure was inhibited. Moreover, the concentration of active and lattice oxygen species was further enhanced. The optimization of the structure and intrinsic properties of the catalyst impels the enhancement of its catalytic performance for soot removal.